Withdrawal of a novel-design duodenoscope ends outbreak of a VIM-2-producing Pseudomonas aeruginosa - Verfaillie, Charlotte J.; Bruno, Marco J.; F. Voor in ’t holt, Anne; Buijs, Jolanda G.; Poley, Jan-Werner; Loeve, Arjo J.; Severin, Juliette A.; Abel, Leo F.; Smit, Bert J.; de Goeij, Inge; Vos, Margreet C. (Endoscopy, 2015)
Background and study aims: Infections are a recognized risk of endoscopic retrograde cholangiopancreatography (ERCP). This paper reports on a large outbreak of VIM-2-producing Pseudomonas aeruginosa that was linked to the use of a recently introduced duodenoscope with a specific modified design (Olympus TJF-Q180V). Methods: Epidemiological investigations and molecular typing were executed in order to identify the source of the outbreak. Audits on implementation of infection control measures were performed. Additional infection control strategies were implemented to prevent further transmission. The design and the ability to clean and disinfect the duodenoscope were evaluated, and the distal tip was dismantled. Results: From January to April 2012, 30 patients with a VIM-2-positive P. aeruginosa were identified, of whom 22 had undergone an ERCP using a specific duodenoscope, the TJF-Q180V. This was a significant increase compared with the hospital-wide baseline level of 2 – 3 cases per month. Clonal relatedness of the VIM-2 P. aeruginosa was confirmed for all 22 cases and for the VIM-2 strain isolated from the recess under the forceps elevator of the duodenoscope. An investigational study of the new modified design, including the dismantling of the duodenoscope tip, revealed that the fixed distal cap hampered cleaning and disinfection, and that the O-ring might not seal the forceps elevator axis sufficiently. The high monthly number of cases decreased below the pre-existing baseline level following withdrawal of the TJF-Q180V device from clinical use. Conclusions: Duodenoscope design modifications may compromise microbiological safety as illustrated by this outbreak. Extensive pre-marketing validation of the reprocessability of any new endoscope design and stringent post-marketing surveillance are therefore mandatory.